2021
DOI: 10.3389/fnagi.2021.743573
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Potential Orchestrators of Alzheimer's Disease-Related Pathologies: Insights on Current Status and Future Possibilities

Abstract: Alzheimer's disease (AD) is a progressive and deleterious neurodegenerative disease, strongly affecting the cognitive functions and memory of seniors worldwide. Around 58% of the affected patients live in low and middle-income countries, with estimates of increasing deaths caused by AD in the coming decade. AD is a multifactor pathology. Mitochondrial function declines in AD brain and is currently emerging as a hallmark of this disease. It has been considered as one of the intracellular processes severely comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 267 publications
(230 reference statements)
0
17
0
Order By: Relevance
“…Because the DAPK1 levels are aberrantly elevated in patients with AD [ 10 , 11 , 16 ], we first investigated the molecular mechanisms regulating DAPK1 expression. MiRNAs have been extensively studied as critical post-transcriptional regulatory factors of gene expression and show promise for the diagnosis and treatment of AD [ 28 , 30 , 31 ]. To determine the potential modulation of DAPK1 expression by miRNAs, we employed bioinformatics databases to predict potential miRNA candidates targeting the 3′ untranslated region (3′UTR) of DAPK1 mRNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the DAPK1 levels are aberrantly elevated in patients with AD [ 10 , 11 , 16 ], we first investigated the molecular mechanisms regulating DAPK1 expression. MiRNAs have been extensively studied as critical post-transcriptional regulatory factors of gene expression and show promise for the diagnosis and treatment of AD [ 28 , 30 , 31 ]. To determine the potential modulation of DAPK1 expression by miRNAs, we employed bioinformatics databases to predict potential miRNA candidates targeting the 3′ untranslated region (3′UTR) of DAPK1 mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Insights into the roles of miRNAs in numerous diseases, including cancer, cardiovascular diseases, and neurological diseases, have contributed to the development of miRNA-based therapeutic strategies [ 25 , 26 ]. Up to 70% of miRNAs are found in the human brain and play important roles in AD-related pathologies [ 27 , 28 , 29 ]. Recent studies have found that miRNA replacement therapies rescue adult hippocampal neurogenesis and memory deficits in AD models [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, it is known that the brain expresses about 70% of experimentally detectable miRNAs [ 155 ].…”
Section: Mirnas As Biomarkers Of the Cognitive Domain Of Frailtymentioning
confidence: 99%
“…Potential therapeutic approaches are, however, not limited to AM strategies. Studies on cell cultures and animal models have also identified compounds that affect miRNA expression [22]. Current commonly used diagnostic methods are primarily based on CSF biomarkers.…”
Section: Introductionmentioning
confidence: 99%